Flowgorithm Sebagai Penunjang Pembelajaran Algoritma dan Pemrograman - Ni Nyoman Emang Smrti; Andisana I Putu Gd Sukenada; Dwi Trisna Rahayu Ni Kadek; Adnan Adnan; Juliantara Pande Putu Ode (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
Technological developments are very fast, there is a lot of software that makes it easier for people to learn. One of them is learning algorithms and programming which studies the stages of effective problem solving so that it can be translated into Programming Language. One of the standards used to describe algorithms is a flowchart. A flowchart is a diagram used to describe in detail the stages of solving a problem. By using a picture of a stage of the problem it will be easier to understand. Many software programs that make it easy to draw flowcharts, one of which is Microsoft Visio. The benefit of Microsoft Visio is that it makes it easier for people to draw flowcharts, but what has been described cannot be known directly. Software that makes it easy to create flowcharts is Flowgorithm. Before Flowgorithm Logic and Algorithm is the basis of this software. Its use is very easy and also free, so this application is widely used by beginners in learning algorithms. Flowcharts created using flowgorithm can be run directly. Flowgorithm can interactively convert flowcharts to more than 18 languages. These include: C#, C++, Java, JavaScript, Lua, Perl, Python, Ruby, Swift, Visual Basic .NET. The purpose of this paper is to provide an alternative to learning programming algorithms before learning programming languages using the flowgorithm application.